2020
DOI: 10.1515/cclm-2020-0981
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of international autoantibody reference standards for the detection of autoantibodies directed against PML bodies, GW bodies, and NuMA protein

Abstract: ObjectivesReference materials are important in the standardization of autoantibody testing and only a few are freely available for many known autoantibodies. Our goal was to develop three reference materials for antibodies to PML bodies/multiple nuclear dots (MND), antibodies to GW bodies (GWB), and antibodies to the nuclear mitotic apparatus (NuMA).MethodsReference materials for identifying autoantibodies to MND (MND-REF), GWB (GWB-REF), and NuMA (NuMA-REF) were obtained from three donors and validated indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Instead, we show a P-value that indicates the statistical significance of the association between the factor as a whole and antibody status, based on an F-test from a statistical contrast. spectrometry, as described in the characterization of other autoantibody reference materials (33)(34)(35). No target antigen was consistently identified, though the data clearly showed that these sera did not recognize DFS70 in either Western blot or immunoprecipitation-mass spectrometry.…”
Section: Discussionmentioning
confidence: 84%
“…Instead, we show a P-value that indicates the statistical significance of the association between the factor as a whole and antibody status, based on an F-test from a statistical contrast. spectrometry, as described in the characterization of other autoantibody reference materials (33)(34)(35). No target antigen was consistently identified, though the data clearly showed that these sera did not recognize DFS70 in either Western blot or immunoprecipitation-mass spectrometry.…”
Section: Discussionmentioning
confidence: 84%
“…MSA is an autoantibody mostly against nuclear mitotic apparatus protein, which is a vital product synthesized by the immune system in the anti‐tumor process. 15 Previous studies by our research group have shown that the MSA level was elevated in SCLC, making it an effective potential auxiliary tool for separating SCLC patients from NSCLC. 16 At the same time, this search yielded plasma MSA concentration in SCLC patients as 92.68 ± 41.86 pg/ ml.…”
Section: Discussionmentioning
confidence: 93%
“…The aberrant expression of those proteins can interfere with the localization of dynein on the spindle and induce spindle multi‐polarization leading to cell cycle instability and accelerating tumor progression. MSA is an autoantibody mostly against nuclear mitotic apparatus protein, which is a vital product synthesized by the immune system in the anti‐tumor process 15 . Previous studies by our research group have shown that the MSA level was elevated in SCLC, making it an effective potential auxiliary tool for separating SCLC patients from NSCLC 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Monoclonal anti-Ro60 IgG antibody A7 was detected in initial screening by ELISA and followed by using HEp-2 IFA. Further characterization of A7 included Western blot analysis using soluble lysate from MOLT-4 cells and a higher ratio of acrylamide monomer as cross-linker in an optimized polyacrylamide gel electrophoresis system (20), immunoprecipitation (IP) with lysate from HeLa cells metabolically labeled with [ 35 S]-methionine (21,22), and also IP using in vitro [ 35 S]-methionine-labeled translation products of Ro60 recombinant cDNA (19). IP was performed in the presence of unconjugated goat anti-mouse IgG/IgM affinity-purified IgG (Jackson ImmunoResearch Lab, West Grove, PA, USA) as a secondary linker to ensure binding of the putative monoclonal antibody to the protein G-Sepharose beads.…”
Section: Monoclonal Antibody Against Ss-a/ro 60-kda Proteinmentioning
confidence: 99%